Sonological Evaluation of Scrotal Pathology by High Resolution Ultrasound and Color Doppler - Narra, Ramakrishna; Pasupuleti, Bhimeswararao; Kumar Kamaraju, Suseel; Jukuri, Naganarasimharaju (International Journal of Medical Research and Review, 2015)
Introduction: The development of sonogram with high frequency linear transducer and color doppler is an important mile stone in evaluating scrotal pathologies. Computed tomography exposes testicles to the radiation and MRI is not so easily available. Therefore ultrasound with color Doppler is the best suited modality for the evaluation of scrotal pathologies as it is simple, noninvasive, reproducible, relatively inexpensive and widely available investigation that will not expose the testis to radiation. Aims and Objectives: To classify (etiologically) and to evaluate various scrotal pathologies using ultrasonography and describe the role of High resolution ultrasound and colour doppler in their diagnosis and differentiation. Materials and Methods: The study was done on 60 patients who were referred to the radiology department by the General Surgery and Urology departments for scrotal ultrasound and Doppler study. This study was conducted between May 2012 to September 2014 at Katuri Medical College and Hospital, Chinnakondrupadu, Guntur. Results : Of the 60 patients studied, incidence of various pathologies were as follows -inflammatory pathology in 26%, congenital in 12%, scrotal hernia in 16%, infertility in 8%, torsion in 7%, tumors in 3.3%, trauma in 3%, and others in 26.7%. The imaging features of these conditions with differentiating hallmarks are described. Conclusion: High frequency ultrasonography is invaluable in demonstrating normalcy of testes and epididymis in the presence of large hydroceles. High-frequency ultrasonography enables clear demonstration of the morphological alterations associated with acute scrotal inflammatory diseases. Color doppler sonography is highly sensitive in diagnosing acute scrotal pathology and accurately differentiates testicular ischemia /torsion from acute inflammatory conditions.